Perencanaan Pembangunan Berbasis Partisipasitif Dalam Penerapan E-Musrenbang - Novita Maulida Ikmal; Beta Ayu Prawesti; Dimas Ayu R; Mali Fajry (FISIP UWP, 2021)
Participatory-Based Development Planning in the Implementation of E-Musrembang. Development planning is a measure of the success of regional development. The passage of a plan cannot be separated from community participation in the implementation of sustainable development planning. Sustainable development or SDGs (Sustainable Development Goals) is a sustainable development agenda promoted by the United Nations (United Nations) as a step to achieve global development. Community involvement in development planning is carried out through the Musrenbang mechanism starting from the village level to the provincial level. The implementation of the Musrenbang is an annual routine agenda carried out by the regional government, especially for the preparation of the Regional Government Work Plan (RKPD) which involves the community at the development planning stage. One form of implementation of E-Government in development planning, the government makes changes, namely in E-Musrembang, the goal is to create transparency and accountability to the government